2017
DOI: 10.1371/journal.pone.0175478
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of hydroxypropyl-beta-cyclodextrins used in the treatment of Niemann-Pick Disease type C1

Abstract: 2-Hydroxypropyl-beta-cyclodextrin (HPβCD) has gained recent attention as a potential therapeutic intervention in the treatment of the rare autosomal-recessive, neurodegenerative lysosomal storage disorder Niemann-Pick Disease Type C1 (NPC1). Notably, HPβCD formulations are not comprised of a single molecular species, but instead are complex mixtures of species with differing degrees of hydroxypropylation of the cyclodextrin ring. The degree of substitution is a critical aspect of the complex mixture as it infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Use of VTS-270 and Trappsol Cyclo has been described in case reports as noted earlier. A recent mass spectrometry study demonstrated significant compositional differences between VTS-270 and another HPβCD product: although both are HPβCDs, they have unique compositional fingerprints and differences in the amounts and types of various ions, monomers, and dimers, and thus should not be considered to be identical [ 33 ]. They may also have different biological and clinical activities and different impurity profiles.…”
Section: Considerations and Future Perspectivesmentioning
confidence: 99%
“…Use of VTS-270 and Trappsol Cyclo has been described in case reports as noted earlier. A recent mass spectrometry study demonstrated significant compositional differences between VTS-270 and another HPβCD product: although both are HPβCDs, they have unique compositional fingerprints and differences in the amounts and types of various ions, monomers, and dimers, and thus should not be considered to be identical [ 33 ]. They may also have different biological and clinical activities and different impurity profiles.…”
Section: Considerations and Future Perspectivesmentioning
confidence: 99%
“…We further characterized the composition of the used HP-β-CD mixture and determined that the most frequent isomer is one with six degrees of substitution (DS) ( Fig EV4A-C). Knowledge of the HP-β-CD composition will leverage application in future clinical trials and facilitate comparisons of treatment results between different neurodegenerative diseases (Yergey et al, 2017).…”
Section: Pink1 Patient-specific Neurons Present a Reduced Mitophagy Cmentioning
confidence: 99%
“…Ion mobility -MS experiments were performed using an Agilent 6560 Ion Mobility -QTOF MS equipped with an Dual Agilent Jet Stream ESI source (Agilent Technologies). The following method is based on a protocol from (Yergey et al, 2017). test was used to evaluate if the samples were drawn from significantly different distributed populations between control and patient lines.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The data suggest that biological and potential therapeutic equivalence should not be assumed. Further studies are needed to examine potential differences in biological and therapeutic effects of Trappsol ® Cyclo™ and VTS-270 [11].…”
Section: Vts-270 (Kleptosementioning
confidence: 99%